SCIENTIFIC-PRACTICAL AND STRATEGIC BASES OF IMPROVING PEDAGOGICAL-PSYCHOLOGICAL COOPERATION IN THE INTEGRATION OF SCHOOL AND PRE-SCHOOL EDUCATIONAL ORGANIZATIONS IN THE CONTEXT OF CONTINUOUS EDUCATION ON THE BASIS OF INNOVATIVE LOGISTICS - Madgapilova Nargiza Talipjanovna (Bright Mind Publishing, 2025)
In this article, innovations in the field of education, educational technologies that develop in education, innovations in the field of education, educational conditions, the requirements of society and the state, traditional pedagogical technologies that implement the ideology of reproductive education, and innovative factors issues of coordination, coordination and development of school and MTT activities are analyzed scientifically and pedagogically
Keywords: Innovative logistics, educational innovations, developmental learning technologies, formation of the educational environment, societal and governmental needs, harmonization of traditional pedagogical technologies with innovative approaches, integration of school and preschool institutions activities